Assessment of MBBS students’ attitudes on social media use: A cross-sectional study in Government Medical College and Hospital, Tiruvannamalai, Tamil Nadu - Nithiya S; Devandiran RS; Kumaran V; Venkatesh G; Sai Sailesh Kumar Goothy (Asian Journal of Medical Sciences, 2023)
Background: The latest internet and social media facilitate communication and increase the speed of work. However, it has a negative side also. Aims and Objectives: The present study aimed to assess the MBBS students’ attitudes toward social media use. Materials and Methods: A total of 322 MBBS students (1st year, 2nd-year, 3rd-year, and final-year students) from Government Thiruvannamalai Medical College were part of the study. Willing students were included in the study. Those students who are not using the smartphone were excluded from the study. Pre-tested semi-structured questionnaires assessing the frequency of social media use and attitudes toward the use of social media in their daily activities were used in the study. Results: Most of the participants belong to 18 and 19 years of age. About 77.3% of participants started using the smartphone at the age of 10–15 years. About 92.8% of participants bought smartphones at age of 15–20 years. About 62.2% were not involved in physical activity. About 55.72% check their phone every 10–20 min. About 84.8% of participants sleep <6 h in 24 h. About 56.9% of participants reported that they will not experience neck pain after prolonged use of smartphones. About 52.3% of the participants reported that they have started using spectacles due to refraction errors after using smartphones. Conclusion: The study results present that students in the medical field are addicted to smartphones and this overuse is associated with significant hazardous events. Hence, students should be counseled to reduce the use of smartphones.